Konstruksi Sosial Pendidikan Seksual pada Orangtua dalam Keluarga Bugis-Makassar - A. Octamaya Tenri Awaru (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
False interpretations of sex make sex education less prioritized by parents in educating their children. This condition is considered as the cause of increased child abuse, violence, and sex crimes. This research aims to reveal the social construction of parents’ sexual education Bugis-Makassar families. The research used a qualitative approach with the paradigm of constructivism. The analysis model was conducted through the interpretation and understanding of data collected through interviews and observations. The informants were selected using a purposive sampling technique with the informants' criteria were the parents in Bugis-Makassar families and have children between the ages of 13-25 years old and also live in the city of Makassar. Data verification was conducted through the persistence of observation and triangulation of time. The data obtained were analyzed through three stages, which consist of data reduction, data presentation, and drawing conclusions. The results showed different construction of each parent according to the level of information and experience they had. Construction occurs simultaneously in three stages, which consist of externalization, objectification, and internalization. The most prominent stage is the objectification stage, which then forms four constructions, which consist of 1) sexual education is teaching about genitals; 2) teaching of sexual intercourse procedures; 3) the distinction of male and female roles, and; 4) the process of teaching manners to associate with the opposite gender. In its implementation, the internalization stage is not maximal due to parental experience, false understanding of sex, fear of parents, child misinterpret the information provided, and lack of knowledge about sexual education.